2013
DOI: 10.1161/circresaha.113.301302
|View full text |Cite
|
Sign up to set email alerts
|

Quaking, an RNA-Binding Protein, Is a Critical Regulator of Vascular Smooth Muscle Cell Phenotype

Abstract: R NA-binding proteins are central regulators of gene expression in both health and disease. 1,2 The RNA-binding protein Quaking (QKI) is a member of the highly conserved signal transduction and activator of RNA (STAR) family of RNA-binding proteins. 3 Alternative splicing of the mammalian qkI transcript yields 3 protein isoforms, notably QKI-5, QKI-6, and QKI-7, 2 with dimerization of QKI isoforms being required for the regulation of pre-mRNA splicing, mRNA export, and stability. 2,4 QKI drives central and per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
120
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(124 citation statements)
references
References 45 publications
3
120
0
Order By: Relevance
“…As an RNA-binding protein, QKI post-transcriptionally regulates the mRNA stability, translation efficiency or RNA transportation of target genes via specifically binding to the cis-elements within the 3'-untranslated region (3'UTR) (6)(7)(8)(9)(10). Among these targets, MAG and MBP, which are essential for postnatal myelination are well characterized.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As an RNA-binding protein, QKI post-transcriptionally regulates the mRNA stability, translation efficiency or RNA transportation of target genes via specifically binding to the cis-elements within the 3'-untranslated region (3'UTR) (6)(7)(8)(9)(10). Among these targets, MAG and MBP, which are essential for postnatal myelination are well characterized.…”
Section: Introductionmentioning
confidence: 99%
“…In adult mammals, qki mRNAs can be detected in tissues, such as the heart, skeletal, lung, testes and immune cells in addition to the central nervous system (CNS) (9,(12)(13)(14)(15). In a search for putative RNA targets recognized by QKI, a bipartite consensus sequence ACUAAY-N(1-20)-UAAY was defined as a QKI response element (QRE), and 1,430 putative mRNA targets were identified by bioinformatic analysis (16).…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that QKI plays an important role in the postnatal central nervous system during myelination. Recent studies suggest that it also plays an essential role in blood vessel development [90]. In addition, van der Veer et al [91] observed that QKI is highly expressed in neointimal VSMCs of human coronary restenoticlesions and neointima hyperplasia of mice.…”
Section: Othersmentioning
confidence: 99%
“…Quaking and VSMC Phenotype (p 1065) 59 Blocking an RNA-binding factor called Quaking prevents vascular smooth muscle cells from over-proliferating, report van der Veer et al…”
Section: Fvbmentioning
confidence: 99%